2018
DOI: 10.1371/journal.pone.0192439
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two mixotrophic chrysophytes: Insights into the metabolisms of two Ochromonas species (Chrysophyceae) through a comparison of gene expression

Abstract: Ochromonas spp. strains CCMP1393 and BG-1 are phagotrophic phytoflagellates with different nutritional strategies. Strain CCMP1393 is an obligate phototroph while strain BG-1 readily grows in continuous darkness in the presence of bacterial prey. Growth and gene expression of strain CCMP1393 were investigated under conditions allowing phagotrophic, mixotrophic, or phototrophic nutrition. The availability of light and bacterial prey led to the differential expression of 42% or 45–59% of all genes, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 48 publications
(63 reference statements)
5
58
1
Order By: Relevance
“…In contrast, in our study, the mixotroph may competitively exclude the phytoplankter even when, in monoculture, its I Ã out is greater, because it is also able to feed on the phytoplankter (Appendix S1: Fig. 3), other studies have shown that prey can enhance mixotroph photosynthetic capacity, perhaps by providing nutrients inaccessible in the culture media (Sanders et al 2001, Lie et al 2018. Because competition for light is mediated by standing stock biomass rather than production of new biomass, the competitive interactions between mixotrophs and phytoplankton mimic interference competition.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…In contrast, in our study, the mixotroph may competitively exclude the phytoplankter even when, in monoculture, its I Ã out is greater, because it is also able to feed on the phytoplankter (Appendix S1: Fig. 3), other studies have shown that prey can enhance mixotroph photosynthetic capacity, perhaps by providing nutrients inaccessible in the culture media (Sanders et al 2001, Lie et al 2018. Because competition for light is mediated by standing stock biomass rather than production of new biomass, the competitive interactions between mixotrophs and phytoplankton mimic interference competition.…”
Section: Discussioncontrasting
confidence: 76%
“…3). These results highlight the complexities of real mixotroph physiology, wherein different taxa may derive different forms and degrees of benefit from ingesting prey (Mitra et al 2016, Lie et al 2018. S5).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations